Analisis Perkembangan Spiritual Anak Usia Dini Kelas A di TK Pembina Agropolitan - Maisarah A.W.A Karim; Rosalinda Lasuku; Sastri Sinde; Wa Ode Mardiyanti; Fiola Indah Putri Pratama (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
This research aims to determine the spiritual development of children in the Agropolitan Kindergarten of Class A. The variables in this research are the children's physical values ​​with development which includes piety, sincerity, obedience and compliance. The sample for this research was 12 children in class A agropolitan kindergartens. Data collection techniques used checklist instruments and direct observation of children in the classroom. The data analysis technique uses the Guttmann scale. The percentage of children's worship scores in agropolitan TKPembina is 99% with a low categorization. The solution given is to instill better religious values ​​because this will determine their future character in accordance with the characteristics of children in agropolitan kindergartens. The implication is that children in supervisory kindergartens receive an educational model that develops spiritually with methods that pay attention to children's religious values. It is hoped that this research can become the basis for further research to be able to develop children's spirituality with perfect values ​​of worship including piety, sincerity, obedience and obedience to the spiritual development model for children in agropolitan kindergartens.